The Influence of Personal Ability, Self-Efficacy and Service Quality on Customer Loyalty with Customer Trust as an Intervening Variable - Artinegar Azmi Ismail; Nurul Azizah (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to analyze and describe the influence of Personal Ability, Self-efficacy and Service Quality on Customer Loyalty with Customer Trust as an intervening variable. The data used in this research is primary data obtained through distributing questionnaires online, and secondary data obtained from the Sahabat Motor of Sukodono Sidoarjo Workshop. The sample in the research consisted of 150 respondents with the criteria of using the Sahabat Motor of Sukodono Sidoarjo Workshop services at least three times. The sampling method used in this research was purposive sampling. This research uses the Statistical Program for Social Science (SPSS) Version 27. The results of this research show that Personal Ability has a positive but not significant effect on Customer Loyalty. Meanwhile, Self-efficacy and Service Quality have a direct positive and significant effect on Customer Loyalty. In this case, Customer trust mediates the influence of Personal Ability, Self-efficacy and Service Quality on Customer Loyalty. This research shows that if the Sahabat Motor of Sukodono Sidoarjo Workshop improves Personal Ability, it will create a sense of loyalty for customers. Customers will also continue to use the services of the Sahabat Motor of Sukodono Sidoarjo Workshop because they can be trusted to meet their needs and handle customer complaints well.